Hubungan Stimulasi Orang Tua Dengan Perkembangan Bicara Dan Bahasa Anak Usia 36-48 Bulan Di Desa Ambarawa Barat - Ismanto, Amatus; Kusuma, Anggi; Palupi, Rini; Puspitasari, Tri (LPPM Universitas Sari Mulia, 2025)
Background: Optimal speech and language development is inseparable from the way parents provide stimulation to their children. Children who get directed stimulation will develop faster than children who lack stimulus. Speech and language development starts from the age of 0-3 years Objective: The purpose of this study was to determine the correlation of parental stimulation with speech and language development of children aged 36-48 months in West Ambarawa Village, Ambarawa Subdistrict, Pringsewu Regency Method: The type of research used is quantitative research with cross sectional research. The population in this study were parents or caregivers and toddlers at the age of 36-48 months in the West Ambarawa Village posyandu, Ambarawa Regency, totaling 207, while the sample taken was 67 respondents. Data analysis was done univariate and bivariate using chi-square test Result: The results of the study obtained parental stimulation with speech and language development with a sig value. 0.000 (sig <0.05). The conclusion of this study is that there is a correlation between speech and language development in toddlers aged 36-48 months in West Ambarawa Village, Ambarawa District, Pringsewu Regency Conclusion: The importance of stimulation from parents that must be done to toddlers about speech and language development